Jacob's ladder : essays on experiences of the ineffable in the context of contemporary psychotherapy - Klein, Josephine (Karnac, 2003)
In this fascinating work, Josephine Klein considers mysticism - a world of ineffable experience - to see if it might have anything to teach those in the therapeutic world and invites the reader to look at newer ways of psychoanalytic thinking. She uses artists and writers of the past to help illuminate contemporary issues.